Oral β-D-glucan potentiates systemic immune responses to intramuscular foot-and-mouth disease vaccination - Kim, Hyeong Won; Park, So Hui; Ko, Mi-Kyeong; Shin, Seokwon; Park, Jong-Hyeon; Lee, Min Ja (Frontiers in Veterinary Science, 2026)
BackgroundFoot-and-mouth disease (FMD) is a viral disease primarily affecting livestock. Although vaccination is the main strategy to control FMD, current commercial FMD vaccines have major drawbacks, such as low antibody titers and short antibody titer maintenance periods. We hypothesized that these shortcomings were caused by low systemic immune induction and the absence of mucosal immune induction by the FMD vaccine.MethodsTo address the limitations, we enhanced adaptive immune responses through the oral administration of β-D-glucan (BDG). We evaluated the systemic and mucosal immune response of the BDG-fed group (BDG intake + FMD vaccine) and control groups (FMD vaccine) in vivo and ex vivo using mice and pigs.ResultsThe results showed that the oral administration of BDG induced long-term antibody and virus-neutralizing antibody titers in mice and pigs through robust cellular and humoral immunity. We showed that the BDG intake stimulates secretory IgA production in mice and pigs. We also showed that mucosal and systemic immunity-related genes were upregulated by the BDG intake.ConclusionIn this study, we provide evidence that the oral administration of BDG improves the overall efficacy of the FMD vaccine by inducing mucosal immunity, which enhances systemic immunity, leading to robust cellular and humoral immune responses in the host. This study is relevant to the establishment of new FMD vaccination strategies, programs, and policies and will contribute to improving field challenges.